2005
DOI: 10.1097/00006982-200512000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Features, and Causes of Vision Loss Among Patients With Ocular Toxocariasis

Abstract: Ocular toxocariasis is an uncommon cause of uveitis that mainly affects younger patients. Inflammation is typically unilateral and presents as either a granuloma in the peripheral or posterior retina or a moderate to severe vitreous inflammation mimicking endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 38 publications
6
138
1
4
Order By: Relevance
“…Um granuloma pode também ocorrer no nervo óptico. Os sinais clínicos mais comuns e os maiores causadores de perda de visão são inflamação vítrea, edema macular cistoide e tração de filamentos vítreo-retinianos em direção ao nervo óptico e/ou um granuloma 85 .…”
Section: Larva Migrans Ocular E Neurológicaunclassified
“…Um granuloma pode também ocorrer no nervo óptico. Os sinais clínicos mais comuns e os maiores causadores de perda de visão são inflamação vítrea, edema macular cistoide e tração de filamentos vítreo-retinianos em direção ao nervo óptico e/ou um granuloma 85 .…”
Section: Larva Migrans Ocular E Neurológicaunclassified
“…The major causes of visual acuity loss are: severe vitreitis (52.6% of the cases), cystoid macular edema (47.4%) and tractional retinal detachment (36.8%) [8]. The real factors that may influence the onset of a determined clinical form are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5 OLM can cause uveitis, posterior and peripheral retinochoroiditis, vitritis, endophthalmitis, papillitis and other ocular lesions that often lead to loss of vision in the affected eye. 2 A deÞ nite diagnosis of OLM is difÞ cult to establish as the larva is rarely identiÞ ed from the lesions. Hence, immunodiagnostic tests have been used as a reliable adjunct for the diagnosis of toxocariasis.…”
Section: Discussionmentioning
confidence: 99%
“…2 The clinical Þ ndings and age of presentation makes differential diagnosis with retinoblastoma necessary, which is at times difÞ cult, although essential, since the treatment and prognosis are very different. Human toxocariasis is highly prevalent in Kashmir valley as indicated by a study, which showed 33.33% population being seropositive (unpublished data).…”
Section: Membersmentioning
confidence: 99%